Dr. Ramprabhu Musham — Deep Plane Facelift — Hyderabad - Musham, Ramprabhu (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ramprabhu Musham, practicing in Hyderabad, India. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003196; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; india; hyderabad